A matter of universalism? Rationalities of access in Finnish early childhood education and care - Salla Fjällström; Kirsti Karila; Maiju Paananen (Taylor & Francis Group, 2020)
Universal access to early childhood education and care (ECEC) has become a policy goal in many countries. In comparing and categorising national ECEC systems, Finnish ECEC has been presented as an example of a universal system. However, as municipalities are responsible for the provision of ECEC services in Finland, it is important to examine how access to ECEC is locally rationalised: how universal is Finnish ECEC after all? Drawing on discursive institutionalism, we analysed what kinds of rationalities administrators of local ECEC services constructed in terms of access to ECEC concerning four-year-old children, and what kind of possible preconditions were constructed in these rationalities. As a result, we found three different but intertwined rationalities of access to ECEC: equality of access for all children, a real need for ECEC, and the parents' choice. The parents' position in the labour market, the level of concern for the child or family, and the parents' decision emerged as constructed preconditions for access. Our examination illustrates the importance of examining local-level policy discourses in order to understand the historical and social constructions of access to ECEC.